2019
DOI: 10.1002/jso.25512
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection in palliative surgery: Defining value

Abstract: Proper patient selection for palliative surgery requires a challenging and often complex decision-making process. Optimally, proposed palliative procedures must be undertaken with an intent to provide the greatest possible value to patients at the end of life. This review describes the process of patient selection and identifies psychosocial, biochemical, and functional markers that can complement sound surgical judgment.impact, palliative surgery, patient selection, value

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…While surgery is often assumed to come at a cost to quality of life, at least during the immediate recovery, a study of palliative surgery patients showed no diminution in quality of life postoperatively, even in those who did not experience tangible benefits (27). In fact, the significant improvements in physical and functional well-being postoperatively are present even in a study where 54% of patients did not achieve the desired operative result (18). The best judge of the value of palliative surgery may be the patients themselves.…”
Section: Risks and Benefits Of Palliative Surgerymentioning
confidence: 97%
See 4 more Smart Citations
“…While surgery is often assumed to come at a cost to quality of life, at least during the immediate recovery, a study of palliative surgery patients showed no diminution in quality of life postoperatively, even in those who did not experience tangible benefits (27). In fact, the significant improvements in physical and functional well-being postoperatively are present even in a study where 54% of patients did not achieve the desired operative result (18). The best judge of the value of palliative surgery may be the patients themselves.…”
Section: Risks and Benefits Of Palliative Surgerymentioning
confidence: 97%
“…Even operations that are generally lowrisk can have substantial risks when applied to palliative patients. The overall mortality rate for percutaneous endoscopic gastrostomy (PEG) tube placement is 0.2% (18). Yet in a retrospective study of patients with malignancyin which 27% of PEG tube placements were for palliative decompression-the procedure was associated with 20% in-hospital mortality (19).…”
Section: Risks and Benefits Of Palliative Surgerymentioning
confidence: 99%
See 3 more Smart Citations